Įvairių tipų impulsinių garso šaltinių akustinės charakteristikos - Stauskis, Vytautas; Kunigėlis, Vytautas (Journal of Civil Engineering and Management, 1998)
Acoustic characteristics of pulsed sound sources of various types The paper examines the acoustic characteristics of explosion-type pulsed sound sources of four types. These include a Calibre 8 sound gun, a start gun, a Calibre 16 hunting gun, and a toy gun. The latter was included both because of its short pulse duration and for comparison purposes. Correct selection of a source is very important because it largely determines the results of acoustic measurements. Certain requirements are set for a sound source. In order to concentrate as much energy as possible at the given moment, the signal bandwidth-duration product must be as large as possible. The range frequencies to be excited depend on the pulse duration. The latter also determines whether interference phenomena will occur in the room and whether individual reflections will merge. The experiments were conducted in a room of 12 m2. The distance between the microphone and the pulsed sound source was 1 m. The structure of reflections depends on the pulse by means of which the sound field is excited. The smallest number of reflections is generated by a sound source. During a 20 ms experiment, the amplitudes of these reflections almost coincided with the direct sound amplitude. A sound gun emits more sound energy than other pulses. When the sound field is excited by means of a start gun and a hunting gun, the reflection structure, by amplitude, is very different from that produced by a sound gun. A dense reflection structure is formed by a toy gun but it emits less energy. The structure of reflections generated by a hunting gun is acceptable but its shots are very unstable, which is a major drawback in an experiment. The shots from a sound gun differ only by about 0.1% among themselves by amplitude, ie they are sufficiently stable. Among the four sound sources, the best reflection structure is produced by a sound gun. A sound gun is characterised both by the longest pulse duration (about 0.55 ms) and the highest levels of energy emitted. The pulse duration of the rest three guns is almost equal and is about 0.15 ms, ie is 3.6 times shorter than that of a sound gun. The forms of signals emitted by these sound sources are also very different. The spectrum of a sound source was established on Fourier transformation basis. The spectrum is largely dependent on the type of a gun by means of which the sound field is excited. The maximum width of the spectrum generated by a sound gun occupies almost two octaves, from 500 to 2000 Hz, and the radiation in this range is quite uniform. The spectra of a start gun and a hunting gun are similar but these guns emit less sound energy than a sound gun. The structure of reflections generated by them is also quite different. A toy gun radiates energy in a less narrower band, the width of which occupies about a half of octave, with a maximum at 2000 Hz. This is not very good because too small quantities of low- and medium-frequency sound energy are radiated. Article in Lithuanian. First Published Online: 26 Jul 2012